Perception of health-related quality of life in elderly subjects living in Chiclayo - Coronado Gálvez, Juan Mavhier (2009)
Introduction: the quality of life related to health is perhaps one of the most objective measure of health. Provides a more comprehensive, integral and valid health status. Objective: The purpose of this study was to assess the perception of Health-Related Quality of Life in elderly adults living in Chiclayo, and to identify the epidemiological characteristics related with such perception. Methods: A cluster sampling method was used, 400 subjects were interviewed using 2 instruments, a social and epidemiological form and a quality of life questionnaire based on the SF-36 Health Survey, and the variables assessed were as follows: physical functioning, physical role, body pain, general health, vitality, social functioning, emotional role, and mental health. Results: Subjects included in the survey were mainly female (56.25%), with a mean age 71.29 ± 7.90 years; more than half of the subjects (52.75%) reported the presence of acute and/or chronic diseases, and 18.3% reported the use of a psychoactive substance (alcohol, tobacco, sedative drugs). With respect to the SF-36 questionnaire, the items physical functioning, mental health, and vitality had the highest rates: 72.75%, 68.74%, and 64.61%, respectively; and the lowest rates were found in general health, physical role, and bodily pain, accounting 50.22%, 61.18%, and 62.22%, respectively. Conclusions: Being male sex, with a higher school grade and having a net income >1,000 Soles (Peruvian Currency) were considered as protective factors; and risk factors included being >80 years of age, having no income-generating activity, not having any health coverage, and having any chronic disease. Values in scale summaries comparing elderly pre-fragile and non-frail Hispanic and American populations were 48.68 ± 7.56, and 54.22 ± 9.56, respectively; the corresponding values for the mental summary scale were 50.94 ± 12.23 and 57.43 ± 11.43, respectively.